The Effect of the Traditional Boy-Boyan Game on the Gross Motor Skills of Children Aged 5-6 Years - Carma Astiana; Rusmayadi Rusmayadi; Angri Lismayani (PG PAUD Universitas Islam Makassar | LP2M-UIM | PPJ PAUD (Perhimpunan Pengelola Jurnal PAUD) Indonesia, 2026)
Gross motor skills are a fundamental aspect of development that needs to be optimally stimulated in early childhood. This study aims to determine the effect of the traditional “boy-boyan” game on the gross motor skills of children aged 5–6 years. This study employed a quantitative approach using a Quasi-Experimental Design and a Nonequivalent Control Group Design. The sample consisted of 20 children selected through purposive sampling, divided into an experimental group of 10 children who received the modified traditional “boy-boyan” game intervention and a control group of 10 children who received the “engklek” game intervention, each for six sessions. The novelty of this study lies in the modification of the “boy-boyan” game using rubber balls and stackable donut rings to enhance safety and visual appeal for children while stimulating basic motor skills. Data were collected through tests, observations, and documentation, then analyzed using descriptive statistics and the Wilcoxon Signed-Rank Test. The results showed that the average gross motor skill score of the experimental group increased from 10.30 on the pre-test to 21.80 on the post-test, with 80% of the children achieving the “Very Good” category. The results of the Wilcoxon test showed an Asymp. Sig. (2-tailed) value of 0.004 < 0.05, leading to the conclusion that the traditional “Boy-Boyan” game has a significant effect on the gross motor skills of 5- to 6-year-old children and is proven to be more effective than the “Engklek” game.